Placing Democratization within the Global Frame: Sociological Approaches to Universalism, and Democratic Contestation in Contemporary Turkey - Rumford, C (BLACKWELL PUBL LTD, 108 COWLEY RD, OXFORD OX4 1JF, OXON, ENGLAND, 2002)
The process of democratization in Turkey is enhanced by both proximity to the European Union's enlargement process and universalistic discourses of personhood rights. and. at the same time, compromised by a nationalistic rejection of global human rights and democratic norms and state-led resistance to political pluralism. One key feature of the democratization process is the way in which contending parties - the Kemalist elite, religious and ethnic minorities, the European Union attempt to legitimise their claims by appeals to universal principles. The paper examines three sociological/social theory approaches to universalism (Beck, Laclau. Robertson) and demonstrates their usefulness for an understanding of political contestation in contemporary Turkey. It is argued that the work of these theorists allows us to move beyond a simplistic polarisation of the universal and the particular, where the state represents the universal and minorities the particular. The conceptualisation of universalism advanced by Beck. Laclau and Robertson points to the need to understand the processes of democratization within a sociologically informed globalization framework.
Keywords: Sociology; sosyoloji